The Species of the Genus Aglaomorpha Schott (Polypodiaceae) in Thailand - BOONKERD, THAWEESAKDI (Tropical Natural History, 2006)
Aglaomorpha coronans (Wall. ex Mett.) Copel. has been known as the only Aglaomorpha species in Thailand for the last 15 years. This study finds that four species may be recognised. Two species, namely A. drynarioides (Hook.) M.C. Roos and A. heraclea (Kunze) Copel., are reported for the first time from peninsular Thailand. Finally, Aglaomorpha acuminata (Willd.) Hovenkamp is a new name for the species previously known as Photinopteris acuminata (Willd.) C. V. Morton. A key to species and line drawings of Aglaomorpha in Thailand are given. The distribution of species is discussed.